INSTITUTIONAL CONSTRAINTS OF HUMAN CAPITAL IN TRANSITION ECONOMIES: WHEN EDUCATION DOES NOT GENERATE GROWTH? - Tmušić, Marko (Economic Outlook, 2026)
This paper analyzes the relationship between education, institutions, and economic growth, with a particular focus on the problem of the mismatch between the accumulation of human capital and the institutional framework governing its utilization. Although a significant body of literature emphasizes the positive role of education in promoting economic development, empirical findings indicate that this relationship is neither universal nor linear. Countries with similar levels of educational attainment often achieve different development outcomes. Drawing on the institutional approach, this paper argues that institutions act as a filter that determines how human capital is utilized and allocated. In the absence of high-quality institutions, education does not necessarily lead to increased productivity but may instead result in the inefficient allocation of resources. This paper develops a conceptual model of the conditional effect and is based on an analysis of existing empirical findings. The results indicate that education has a significant positive impact on growth primarily in countries with high institutional quality, whereas this effect is limited within weaker institutional frameworks. The paper’s particular contribution lies in the integration of human capital theory and institutional economics, as well as in emphasizing the conditional nature of education as a factor of economic growth.
Keywords: human capital, institutions, economic growth, education–labour market mismatch, brain drain, innovation, productivity, transition economies, Western Balkans, Serbia.